Chemical Composition of the Essential oil of Brocchia cinerea Grown in South Eastern of Algeria - Bouziane, M.; Badjah-Hadj-Ahmed, Y.; Hadj-mahammed, M. (Asian Journal of Chemistry, 2013)
The aerial parts of Brocchia cinerea collected from the region of Ouargla, which is located in the southeastern of Algeria, were investigated to obtain the essential oil of this plant by hydrodistillation method. The first sample HE1 was obtained by decantation of the distillate while the second HE2 was extracted from the distillate by n-hexane. The samples were analyzed by GC-FID on two capillary columns: a non-polar (HP1) and a polar one (Innowax). The HE1 extract was also analyzed by GC-MS on a DB5 column. The two samples presented nearly the same composition, the main components identified in both were: thujone (47.72 %), camphor (10.54 %), santolinatriene (8.00 %), eucalyptol (6.37 %) and in second order lyratyl acetate (4.17 %), terpinen-4-ol (2.77 %).